Biventricular Impella (Bi-Pella) in Refractory Cardiogenic Shock: The First Case from the Middle East - Abdulaziz Almejren; Abdullah Alenezi (Case Reports in Medicine)
Cardiogenic shock (CS) associated with biventricular failure (BiVF) carries significant in-hospital morbidity and mortality. We describe here the successful use of percutaneous biventricular Impella (Bi-Pella) for cardiogenic shock secondary to acute biventricular myocardial infarctions (AMI-CS), as guided by parameters such as mixed venous oxygen saturation (SvO2), pulmonary artery pulsatility index (PAPi), central venous pressure (CVP), and cardiac power output (CPO). We aim to highlight the promising outcomes of timely implanted biventricular Impella in (AMI-CS).